Effect of an antimicrobial stewardship program in the prevention of antibiotic misuse in patients with spinal cord injury undergoing minor urologic procedures: a single-group, quasi-experiment study - Lina I. Alnajjar; Nourah S. Alrashidi; Njoud Almutairi; Noura Alshamrani; Omar S. Khan; Sajjad Ali; Amira M Youssef; Reem Binsuwaidan (BMC Infectious Diseases, 2023)
Abstract Background Antimicrobial stewardship programs (ASPs) are an internationally recognized strategy for reducing antimicrobial resistance while maintaining patient safety. ASP activities include the restriction of broad-spectrum antibiotics, the establishment of hospital guidelines based on antibiograms, and the promotion of appropriate antibiotic use. This study aimed to determine whether the implementation of antimicrobial stewardship practices improved the effects of a peri-procedure antibiotic prophylaxis prescribed by urologists for patients with spinal cord injury/disease (SCI/D) undergoing minor urological procedures at a tertiary care hospital. Methods This single-group, quasi-experiment study included adult patients with SCI/D who required minor urological procedures (cystoscopy, cytobotox, cystolitholapaxy, and urodynamic study) and who were hospitalized between 2012 and 2020. Results In total, 233 patients were included in each of the pre- and post-ASP implantation groups. There was a significant reduction in antibiotic use among patients who received a pre-procedure antimicrobial prophylaxis in the post- compared to the pre-implementation group (45.9% vs. 24.46%, p < 0.0001), and there was a highly significant reduction in the post- compared to the pre-implementation group in the number who received a post-procedure prophylaxis (16.7% vs. 1.2%, p < 0.0001). Conclusion ASP implementation is a highly effective strategy for reducing the use of peri-procedure antimicrobial prophylaxes in patients with SCI/D injuries undergoing minor urological procedures.